KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XII PADA MATERI PROGRAM LINIER - Citra Nurani Putri; Dori Lukman Hakim (IKIP Siliwangi, 2022)
This article discusses the analaisis of students' mathematical concept comprehension ability in the Linear Program material. The subjects of this study were 8 students of class XII science 2 at SMAN 2 Telukjambe Timur. This research uses qualitative descriptive method. The instrument in this study is in the form of a description test instrument of 4 questions that contain indicators of understanding concepts. The analytical techniques used are data reduction, presenting data, and drawing conclusions. And the results of this study, in the excellent category there is 1 student with a percentage of 12.5%, the good category there are 2 students with a percentage of 25%, in the sufficient category there are 2 students with a percentage of 25%, the bad category there is 1 student with a percentage of 12.5%, and for the very bad category there are 2 students with a very bad category with a percentage of 25%. So, if we look at the average score, it can be concluded that the ability to understand students' mathematical concepts in this study is in the sufficient category.